Determinants of Hemodialysis Treatment Adherence Among Patients With Chronic Kidney Failure at Hermina Manado Hospital - Tooy, Merdike Pertiwi; Manampiring, Aaltje; Homenta, Heriyannis (Journal of Scientific Insights, 2026)
Adherence to hemodialysis therapy is essential for improving clinical outcomes and reducing complications among patients with chronic kidney failure; however, non-adherence remains a persistent challenge in many healthcare facilities. This study aimed to analyze the factors influencing adherence to hemodialysis among chronic kidney failure patients at Hermina Manado Hospital. A quantitative analytical cross-sectional design was employed, involving patients undergoing routine hemodialysis. Data were collected using a structured questionnaire covering sociodemographic characteristics, knowledge level, family support, service accessibility, and patient perceptions of therapy. Logistic regression analysis was conducted to identify key determinants of adherence. The findings showed that sociodemographic factors (age, gender, and education) showed no significant association with hemodialysis adherence. In contrast, internal and social factors demonstrated strong relationships with compliance. Higher patient knowledge was significantly associated with better adherence, as were strong family support and higher motivation levels. Multivariate analysis identified knowledge as the dominant predictor of compliance, with patients possessing good knowledge being 3.49 times more likely to adhere to treatment than those with lower knowledge. This study concludes that adherence can be improved through comprehensive strategies aimed at increasing patient knowledge, optimizing family support, and enhancing service accessibility, thereby contributing to better hemodialysis outcomes and overall patient well-being.